2022
DOI: 10.7554/elife.80014
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteomic mapping reveals distinct signaling actions and activation of muscle protein synthesis by Isthmin-1

Abstract: The secreted protein Isthmin-1 (Ism1) mitigates diabetes by increasing adipocyte and skeletal muscle glucose uptake by activating the PI3K-Akt pathway. However, while both Ism1 and insulin converge on these common targets, Ism1 has distinct cellular actions suggesting divergence in downstream intracellular signaling pathways. To understand the biological complexity of Ism1 signaling, we performed phosphoproteomic analysis after acute exposure, revealing overlapping and distinct pathways of Ism1 and insulin. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Skeletal muscle not only controls whole-body energy expenditure, but also serves as a reservoir of protein and is highly sensitive to protein anabolism and catabolism. Recent studies have shown that ISM1 can act directly on skeletal muscle cells to induce protein synthesis via pAKT- pS6 S235/S236 (Zhao et al 2022 ). Skeletal muscle fibers became smaller, protein degradation increased, muscle strength decreased, and muscle atrophy-related FOXO1 target gene levels increased with ISM1 knockdown (Zhao et al 2022 ).…”
Section: Biological Function Of Ism1mentioning
confidence: 99%
See 1 more Smart Citation
“…Skeletal muscle not only controls whole-body energy expenditure, but also serves as a reservoir of protein and is highly sensitive to protein anabolism and catabolism. Recent studies have shown that ISM1 can act directly on skeletal muscle cells to induce protein synthesis via pAKT- pS6 S235/S236 (Zhao et al 2022 ). Skeletal muscle fibers became smaller, protein degradation increased, muscle strength decreased, and muscle atrophy-related FOXO1 target gene levels increased with ISM1 knockdown (Zhao et al 2022 ).…”
Section: Biological Function Of Ism1mentioning
confidence: 99%
“…Recent studies have shown that ISM1 can act directly on skeletal muscle cells to induce protein synthesis via pAKT- pS6 S235/S236 (Zhao et al 2022 ). Skeletal muscle fibers became smaller, protein degradation increased, muscle strength decreased, and muscle atrophy-related FOXO1 target gene levels increased with ISM1 knockdown (Zhao et al 2022 ). This suggests that ISM1 may affect the contractile function of skeletal muscle by regulating its protein synthesis.…”
Section: Biological Function Of Ism1mentioning
confidence: 99%